CLINICAL COURSE OF ACUTE SINUSITIS (ACUTUS SINUSITIS). (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The purpose of the study is to study the clinical course of acute sinusitis and to identify and implement new approaches to its treatment.